Composite heat-conducting and sound-absorbing material as well as preparation method and application thereof
By filling the porous matrix with sound-absorbing materials and forming a three-dimensional mesh structure of thermal aerogel, the existing sound-absorbing materials have been solved, and the efficient sound-absorbing and thermal conductivity is achieved, which improves the reliability and application prospects of the product.
Patent Information
- Application Number
- CN202411635009.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-28
AI Technical Summary
The thermal conductivity of existing sound-absorbing materials is poor, which makes it difficult for speakers to dissipate heat. At the same time, the sound-absorbing particles are prone to powder loss and powder leakage, requiring a high-cost powder filling process configuration.
By filling the sound-absorbing material in the porous substrate and forming a thermally conductive aerogel in situ between the porous substrate and the sound-absorbing material, a three-dimensional network structure is formed to fix the sound-absorbing material and improve the specific surface area and thermal conductivity.
It realizes effective fixing of sound-absorbing materials without the need for adhesives, improves sound-absorbing effect and thermal conductivity, and enhances product reliability and application prospects.
Smart Images

Figure CN119541435A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sound-absorbing materials, and in particular to a composite heat-conductive sound-absorbing material and a preparation method and application thereof. Background Art
[0002] With the development of technology, the service life of smartphones has been greatly increased. However, the general demand for smartphones to be portable and thin has made the internal design space of mobile phones smaller and smaller. As one of the important components, the increase in the volume of the speaker's back cavity can not only bring a large bandwidth, but also improve the low-frequency characteristics, giving users a better acoustic experience and low-frequency impact. Therefore, mobile phone manufacturers generally fill the speaker's back cavity with sound-absorbing materials to increase the equivalent back cavity volume, such as molecular sieve sound-absorbing particles, sound-absorbing cotton, etc. However, the thermal conductivity of existing sound-absorbing materials on the market is generally poor, which is a huge challenge for the heat dissipation of speakers. In addition, the sound-absorbing particles are prone to powder loss and leakage, and need to be configured through a powder filling process, which has high equipment and process costs.
[0003] In order to improve the heat dissipation problem of speakers, thermal conductive materials such as graphene, carbon nanotubes, and carbon fibers are currently introduced to enhance the heat dissipation capacity of sound-absorbing particles. However, the specific surface area of such thermal conductive materials is much smaller than that of sound-absorbing particles. Under the same volume conditions, the sound absorption effect of the composite material formed by blending high thermal conductive materials and sound-absorbing particles is not as good as that of single sound-absorbing particles. In addition, in order to reduce the adverse effects of powder loss and leakage on heat dissipation and sound absorption, adhesives are usually introduced during the molding process to bond high thermal conductive materials and sound-absorbing particles. The introduction of adhesives will reduce the specific surface area of the molecular sieve and affect the sound absorption effect of the sound-absorbing particles. In addition, adhesives are usually polymer materials with poor thermal conductivity, which will further affect the thermal conductivity of the composite material.
[0004] Based on this, there is an urgent need for a composite thermally conductive and sound-absorbing material that has both high thermal conductivity and excellent sound absorption effects to meet the sound absorption and heat dissipation needs of electronic devices such as speakers. Summary of the invention
[0005] To solve the above problems, the present invention provides a composite thermally conductive sound-absorbing material and a preparation method and application thereof. The present invention fills the sound-absorbing material into a porous matrix and in-situ forms aerogel between the porous matrix and the sound-absorbing material. The three-dimensional network structure formed by the interweaving of the aerogel can effectively fix the sound-absorbing material without using an adhesive to prevent it from falling off. At the same time, the introduction of aerogel can increase the specific surface area of the product, thereby further improving the sound absorption effect of the product. In addition, the thermally conductive aerogel with a three-dimensional network structure can also improve the thermal conductivity of the product, so that the product has good application prospects in electronic devices with sound absorption and heat dissipation requirements such as speakers.
[0006] Specifically, the following technical solutions are provided:
[0007] A first aspect of the present invention provides a composite heat-conductive sound-absorbing material, the composite heat-conductive sound-absorbing material comprising a porous matrix, a sound-absorbing material filled in the pores of the porous matrix, and a heat-conductive aerogel formed in the pores of the porous matrix;
[0008] The thermally conductive aerogel is filled in the gap between the porous matrix and the sound absorbing material and / or in the gap between the sound absorbing materials, and is interwoven to form a three-dimensional network structure.
[0009] Furthermore, the porous matrix is preferably polymer foam, foam metal or porous carbon material, such as polyurethane sound-absorbing foam, but is not limited to the types listed above, and may also be other substrates with a porous structure.
[0010] Furthermore, the sound absorbing material includes but is not limited to one or more of molecular sieve powder, mesoporous silica, carbon nanotubes, and carbon black, such as ZSM-5 molecular sieve.
[0011] Furthermore, the thermally conductive aerogel comprises a thermally conductive material, and the thermally conductive material is preferably a one-dimensional nanomaterial, which can be selected from one or more of silver nanowires, gold nanowires, copper nanowires, carbon nanotubes, and carbon fibers, but is not limited to the thermally conductive materials listed above.
[0012] In some preferred embodiments of the present invention, the size of the sound-absorbing material is smaller than the pore size of the porous matrix, and the size of the thermally conductive material is preferably smaller than the pore size of the porous matrix, so that the sound-absorbing material and the thermally conductive material can enter the pores of the porous matrix; preferably, the pore size of the porous matrix is 50-500 μm, the size of the sound-absorbing material is 1-10 μm, and the size of the thermally conductive material is 15-50 μm, and the above sizes are the average particle size of granular materials, the average length of one-dimensional materials, or the average diameter of two-dimensional materials.
[0013] The second aspect of the present invention provides a method for preparing the composite heat-conductive and sound-absorbing material according to the first aspect, comprising the following steps:
[0014] S1, immersing the porous substrate in a dispersion of a sound-absorbing material, taking it out and drying it, to obtain a modified porous substrate in which the pores are filled with the sound-absorbing material;
[0015] S2. Providing a thermally conductive aerogel precursor slurry A, wherein the thermally conductive aerogel precursor slurry A comprises a thermally conductive material, a cross-linking agent and a dispersant, immersing the modified porous matrix in the thermally conductive aerogel precursor slurry A, and using an ice crystal template method and freeze drying or supercritical drying treatment to form a thermally conductive aerogel from the thermally conductive aerogel precursor slurry A filled in the modified porous matrix, thereby obtaining the composite thermally conductive sound-absorbing material; or,
[0016] A thermally conductive aerogel precursor slurry B is provided, wherein the thermally conductive aerogel precursor slurry B comprises a metal salt, a surface modifier, a reducing agent and a catalyst, the modified porous substrate is immersed in the thermally conductive aerogel precursor slurry B, and a thermally conductive aerogel is formed in the pores of the modified porous substrate through in-situ self-assembly and freeze-drying or supercritical drying treatment to obtain the composite thermally conductive sound-absorbing material.
[0017] The present invention first fills the pores of a porous matrix with sound-absorbing material, and then constructs thermal conductive aerogel in situ in the gaps between the porous matrix and the sound-absorbing material and in the gaps between the sound-absorbing materials in the pores of the porous matrix, so that as much space as possible in the pores of the porous matrix is occupied by the sound-absorbing material to improve the sound absorption effect.
[0018] Furthermore, in S1, the mass concentration of the sound absorbing material dispersion is 1-50wt%, for example, 1wt%, 5wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, 45wt%, 50wt%, etc., including but not limited to the mass concentrations listed above.
[0019] Furthermore, in S1, the impregnation time is 5-30 minutes; preferably, ultrasonic treatment is performed during the impregnation process to assist the sound-absorbing material to enter the pores of the porous matrix.
[0020] Furthermore, in S1, the drying temperature is 100-150 degrees, and the drying time is 3-30 minutes.
[0021] Furthermore, in S2, the mass concentration of the thermally conductive material in the thermally conductive aerogel precursor slurry A is 0.1-10wt%; preferably, the thermally conductive material is nanosilver wire, and the cross-linking agent is PVA; the dispersant in the aerogel precursor slurry A comprises ethanol and water.
[0022] In some preferred embodiments, the preparation method of the thermal conductive aerogel precursor slurry A is specifically as follows: dissolving PVA in water to obtain a PVA solution; mixing the PVA solution and the nano silver wire dispersion evenly, vortexing and centrifuging to remove the supernatant, and then adding the PVA solution to dilute to obtain the aerogel precursor slurry A.
[0023] Furthermore, in S2, the modified porous matrix is immersed in the thermal conductive aerogel precursor slurry A for 5-10 minutes; preferably, ultrasonic treatment is performed during the immersion process to assist the thermal conductive aerogel precursor slurry A to enter the pores of the modified porous matrix.
[0024] Furthermore, in S2, the ice crystal template method is specifically as follows: the modified porous matrix after impregnation is taken out, placed on a pre-cooled substrate, and the modified porous matrix filled with thermal conductive aerogel precursor slurry A is crystallized from bottom to top, and after complete crystallization, freeze drying or supercritical drying treatment is performed.
[0025] The present invention adopts the ice crystal template method to make the thermally conductive aerogel precursor slurry A in the modified porous matrix rapidly solidify into ice crystals at one end close to the pre-cooled matrix, and under the action of temperature difference, grow along the solidification direction to form parallel ice columns, and the one-dimensional thermally conductive material dispersed in the slurry is squeezed by the parallel growing ice columns to form a layer of two-dimensional network of thermally conductive material between the ice columns, and the two-dimensional sheets in the entire frozen body are interconnected to form a three-dimensional thermally conductive network structure that is interconnected. After freeze drying, a self-supporting aerogel structure is formed, which can be used to fix sound-absorbing materials. If the modified porous matrix filled with thermally conductive aerogel precursor slurry A is directly placed under low temperature conditions for freezing treatment before freeze drying, the grain boundaries of the ice crystals formed are randomly distributed, and the dry product formed after freeze drying cannot play a self-supporting role.
[0026] Further, in S2, the concentration of the metal salt in the thermally conductive aerogel precursor slurry B is 0.1-100 mmol / L, preferably, the metal salt is silver nitrate, the surface modifier is PVP, the reducing agent is at least one of ferric chloride, sodium chloride, and copper chloride, and the catalyst is ethylene glycol. The reducing agent is also used as a morphology control agent for the nano silver wires, and reducing agents of different formulations are selected to control the morphology of the nano silver wires.
[0027] Furthermore, in S2, the in-situ self-assembly is specifically: immersing the modified porous matrix in the aerogel precursor slurry B, performing a heating reduction reaction, and the metal salt is in-situ reduced in the pores of the modified porous matrix to form one-dimensional metal nanowires.
[0028] In some preferred embodiments, when the metal salt in the aerogel precursor slurry B is silver nitrate, the heating reduction reaction includes a preheating stage and a heat preservation stage, the temperature of the preheating stage is 70-90 degrees, the time is 60-120 minutes, and the temperature of the heat preservation stage is 120-160 degrees, and the time is 1-8 hours.
[0029] A third aspect of the present invention provides a speaker, comprising a sound absorbing material fixedly disposed in the speaker housing, wherein the sound absorbing material is the composite thermal conductive sound absorbing material described in the first aspect or the composite thermal conductive sound absorbing material prepared by the preparation method described in the second aspect.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] The present invention provides a composite thermally conductive sound-absorbing material, which takes a porous material as a matrix, and fills the sound-absorbing material in the porous matrix to improve the sound-absorbing effect of the porous matrix; on this basis, by in-situ forming aerogel between the porous matrix and the sound-absorbing material, the three-dimensional mesh structure formed by the interweaving of the aerogel plays a role in supporting and fixing the sound-absorbing material, and can effectively fix the sound-absorbing material without the need for an adhesive, so as to prevent the sound-absorbing material from falling off during use, thereby increasing reliability; secondly, the aerogel filled in the gap between the porous matrix and the sound-absorbing material and in the gap between the sound-absorbing materials increases the specific surface area in the effective space of the product, thereby further improving the sound-absorbing effect of the product; in addition, the thermally conductive aerogel forms a three-dimensional thermally conductive network in the composite thermally conductive sound-absorbing material, which can effectively improve the thermal conductivity and heat dissipation capacity of the product. The above-mentioned composite thermally conductive sound-absorbing material has both high thermal conductivity and excellent sound absorption effect, and the product has good reliability, so that the composite thermally conductive sound-absorbing material has good application prospects in electronic devices with sound absorption and heat dissipation requirements such as speakers.
[0032] The present invention also provides a method for preparing the composite thermally conductive sound-absorbing material. The composite thermally conductive sound-absorbing material that does not require a binder, has a stable structure, and has excellent sound absorption and thermal conductivity can be prepared by simple impregnation, ice crystal template method / in-situ reduction, freeze drying / supercritical drying. The preparation method is simple and easy to operate. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 A schematic diagram of the local structure of the internal pores of the composite heat-conductive and sound-absorbing material prepared in Example 1;
[0034] Icon: 1 is the inner wall of the pore, 2 is the sound-absorbing material, and 3 is the thermal conductive aerogel. DETAILED DESCRIPTION
[0035] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art to which the present invention belongs. The terms used herein in the specification of the present invention are for the purpose of describing specific embodiments only and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items. The term "includes" or "comprising" described in the present invention means that it may include or contain other components in addition to the components described. The term "includes" or "comprising" described in the present invention may also be replaced by the closed form "for" or "consisting of..."
[0036] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.
[0037] Example 1
[0038] This embodiment provides a composite heat-conducting and sound-absorbing material and a preparation method thereof, and the specific operations are as follows:
[0039] (1) soaking the polyurethane foam in a ZSM-5 molecular sieve dispersion with a mass concentration of 10%, and using ultrasonic dispersion to assist the molecular sieve to enter the internal pores of the polyurethane foam. The soaking time is 5 minutes, and then the foam is taken out and placed on a sieve, and then baked in an oven at 120° C. for 10 minutes to obtain a modified foam matrix;
[0040] (2) PVA was added to deionized water at a ratio of 1 g PVA: 100 mL water, and heated and stirred in a 90-degree water bath until completely dissolved to obtain a 10 mg / mL PVA solution B for standby use; 100 mL PVA solution B was mixed with 20 mL of 10 mg / mL nanosilver wire ethanol dispersion, and after vortexing, the mixture was centrifuged at 5000 rpm for 10 min. After removing the supernatant, the solution B was added to dilute the mixture to 10 mL to obtain a nanosilver wire / PVA slurry;
[0041] The modified foam matrix is immersed in the nanosilver wire / PVA slurry C. Ultrasonic dispersion can be used to assist the slurry C to enter the internal pores of the modified foam matrix. The immersion time is 5 minutes. Then it is taken out and placed on a copper block pre-cooled in liquid nitrogen. The foam crystallizes from bottom to top. After complete crystallization, it is quickly placed in a freeze dryer and dried at low temperature for 48 hours (-50°C, 5Pa) under vacuum to obtain a composite thermal conductive and sound-absorbing material based on aerogel.
[0042] Example 2
[0043] This embodiment provides a composite heat-conducting and sound-absorbing material and a preparation method thereof, and the specific operations are as follows:
[0044] (1) soaking the polyurethane foam in a ZSM-5 molecular sieve dispersion with a mass concentration of 10%, and using ultrasonic dispersion to assist the molecular sieve to enter the internal pores of the polyurethane foam. The soaking time is 5 minutes, and then the foam is taken out and placed on a sieve, and then baked in an oven at 120° C. for 10 minutes to obtain a modified foam matrix;
[0045] (2) Add 0.2 g of PVP to 25 mL of ethylene glycol, heat and stir in a 90-degree water bath until completely dissolved, and obtain 8 mg / mL of PVP solution B for use; add 0.25 g of silver nitrate and 4 mL of 2 mmol / mL ferric chloride solution to PVP solution B and mix well to obtain an aerogel precursor slurry;
[0046] The modified foam matrix was immersed in the aerogel precursor slurry in the third step, and placed in a blast drying oven with a reactor as a container for preheating at 130°C for 30 minutes, and then the temperature was adjusted to 140°C, kept warm for 4 hours, and then cooled with the furnace. After washing with ethanol at a flow rate of 10 mL / min for 6 hours, CO2 supercritical drying was performed to obtain a composite thermal conductive sound absorbing material.
[0047] Example 3
[0048] This embodiment relates to a composite thermally conductive sound-absorbing material and a preparation method thereof, which is different from Embodiment 1 only in that an equal amount of ZSM-5 molecular sieve is dispersed in a nano silver wire / PVA slurry, and subjected to a one-step impregnation treatment, and the remaining operations are the same to obtain a composite thermally conductive sound-absorbing material.
[0049] Comparative Example 1
[0050] This comparative example relates to the preparation of a composite heat-conductive sound-absorbing material, which is different from Example 1 only in that a direct freezing method is used to replace the ice crystal template method in Example 1 for freezing treatment, and the rest is the same to obtain a composite heat-conductive sound-absorbing material.
[0051] Comparative Example 2
[0052] The comparative example relates to the preparation of a composite thermally conductive sound-absorbing material, which is different from Example 1 only in that: ZSM-5 molecular sieve, nano silver wire ethanol dispersion, and binder (acrylate adhesive) are mixed according to the mass ratio of ZSM-5 molecular sieve, nano silver wire, and binder of 10:10:1 to obtain a mixed solution, polyurethane foam is immersed in the mixed solution, and ultrasonic dispersion is used to assist slurry C to enter the internal pores of the modified foam matrix. The immersion time is 5 minutes, and the other operations are the same to obtain a composite thermally conductive sound-absorbing material.
[0053] Performance Testing
[0054] The thermal conductivity, sound absorption performance and stability of the composite thermally conductive and sound-absorbing materials prepared in the above embodiments and comparative examples were tested. The specific test process is as follows:
[0055] Thermal conductivity test: thermal conductivity is tested by laser flash method;
[0056] Sound absorption performance test: ISO010534-2 "Measurement of sound absorption coefficient and acoustic impedance in acoustic impedance tubes Part 2: Transfer function method";
[0057] Stability test: Place the composite thermal conductive and sound absorbing material at 85°C / 85RH% for 168 hours, take it out of the high temperature and high humidity chamber and place it for 24 hours, then test the thermal conductivity and sound absorption performance of the composite thermal conductive and sound absorbing material using the above test method;
[0058] The test results are shown in Table 1 below:
[0059] Table 1
[0060]
[0061]
[0062] As can be seen from Table 1, compared with the composite thermally conductive and sound-absorbing material formed by fixing the thermally conductive material and the sound-absorbing material in the pores of the polyurethane foam using an adhesive in Comparative Example 2, the composite thermally conductive and sound-absorbing materials prepared in Examples 1-3 have high thermal conductivity and high sound absorption coefficient, wherein the sound absorption coefficient is increased by more than double. This is because the adhesive used in Comparative Example 2 will block some of the pores of the foam and the sound-absorbing material, resulting in relatively poor sound absorption effect, and the adhesive has low thermal conductivity, which affects the overall thermal conductivity.
[0063] It can be seen from Example 1 and Comparative Example 1 that the composite thermally conductive and sound-absorbing material prepared by the conventional freezing method has poor structural stability. After the freezing is completed, the nano silver wire network structure formed inside will collapse due to its lack of self-supporting ability, causing the nano silver wire to be directly adsorbed on the surface of the sound-absorbing particles. In addition, a large number of holes exist in the composite thermally conductive and sound-absorbing material prepared by this method, which is similar to "broken bridge aluminum", thereby interrupting the heat conduction path and reducing the specific surface area, resulting in poor thermal conductivity and sound absorption effects of the composite thermally conductive and sound-absorbing material.
[0064] The above-described embodiments are only preferred embodiments for fully illustrating the present invention, and the protection scope of the present invention is not limited thereto. Equivalent substitutions or changes made by those skilled in the art based on the present invention are within the protection scope of the present invention. The protection scope of the present invention shall be subject to the claims.
Claims
1. A composite heat-conducting and sound-absorbing material, characterized in that: The composite heat-conductive sound-absorbing material comprises a porous matrix, a sound-absorbing material filled in the pores of the porous matrix, and a heat-conductive aerogel formed in the pores of the porous matrix; The thermally conductive aerogel is filled in the gap between the porous matrix and the sound absorbing material and / or in the gap between the sound absorbing materials, and is interwoven to form a three-dimensional network structure.
2. The composite heat-conducting and sound-absorbing material according to claim 1, characterized in that: The porous matrix is a polymer foam, a foam metal or a porous carbon material; The sound absorbing material is selected from one or more of molecular sieve powder, mesoporous silica, carbon nanotubes, and carbon black; The thermally conductive aerogel comprises a thermally conductive material, and the thermally conductive material is a one-dimensional nanomaterial selected from one or more of silver nanowires, gold nanowires, copper nanowires, carbon nanotubes, and carbon fibers.
3. The composite heat-conducting and sound-absorbing material according to claim 2, characterized in that: The pore size of the porous matrix is 50-500 μm; The size of the sound absorbing material is 1-10 μm; The size of the thermal conductive material is 15-50 μm; The size is the average particle size for a granular material or the average length for a one-dimensional material.
4. A method for preparing the composite heat-conducting and sound-absorbing material according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1, immersing the porous substrate in a dispersion of a sound-absorbing material, taking it out and drying it, to obtain a modified porous substrate in which the pores are filled with the sound-absorbing material; S2, providing a thermally conductive aerogel precursor slurry A, wherein the thermally conductive aerogel precursor slurry A comprises a thermally conductive material, a cross-linking agent and a dispersant, immersing the modified porous matrix in the thermally conductive aerogel precursor slurry A, and forming a thermally conductive aerogel from the thermally conductive aerogel precursor slurry A filled in the modified porous matrix by an ice crystal template method and a drying treatment, wherein the drying treatment is a freeze drying treatment or a supercritical drying treatment, to obtain the composite thermally conductive sound-absorbing material; or, A thermally conductive aerogel precursor slurry B is provided, wherein the thermally conductive aerogel precursor slurry B comprises a metal salt, a surface modifier, a reducing agent and a catalyst, the modified porous substrate is immersed in the thermally conductive aerogel precursor slurry B, and a thermally conductive aerogel is formed in the pores of the modified porous substrate through in-situ self-assembly and drying treatment, wherein the drying treatment is a freeze-drying treatment or a supercritical drying treatment, to obtain the composite thermally conductive sound-absorbing material.
5. The preparation method according to claim 4, characterized in that: S1 contains at least one of the following features: (1) The mass concentration of the sound absorbing material dispersion is 1-50wt%; (2) The immersion time is 5-30 min; (3) performing ultrasonic treatment during the impregnation process to assist the sound absorbing material to enter the pores of the porous matrix; (4) The drying temperature is 100-150 degrees, and the drying time is 3-30 minutes.
6. The preparation method according to claim 4, characterized in that: In S2, the mass concentration of the thermal conductive material in the aerogel precursor slurry A is 0.1-10wt%; Preferably, the thermally conductive material is nanosilver wire, the cross-linking agent is PVA, and the dispersant comprises ethanol and water.
7. The preparation method according to claim 4, characterized in that: In S2, the modified porous substrate is immersed in the thermally conductive aerogel precursor slurry A for 5-10 minutes; preferably, ultrasonic treatment is performed during the immersion process to assist the thermally conductive aerogel precursor slurry A to enter the pores of the modified porous substrate; The ice crystal template method is specifically as follows: the modified porous matrix after impregnation is taken out and placed on a pre-cooled substrate, and the modified porous matrix filled with thermally conductive aerogel precursor slurry A is crystallized from bottom to top, and after complete crystallization, freeze drying or supercritical drying is performed.
8. The preparation method according to claim 4, characterized in that: In S2, the concentration of the metal salt in the thermally conductive aerogel precursor slurry B is 0.1-100 mmol / L; Preferably, the metal salt is silver nitrate, the surface modifier is PVP, the reducing agent is at least one of ferric chloride, sodium chloride and cupric chloride, and the catalyst is ethylene glycol.
9. The preparation method according to claim 4, characterized in that: In S2, the in-situ self-assembly is specifically as follows: the modified porous matrix is immersed in the thermally conductive aerogel precursor slurry B, and a heating reduction reaction is performed, so that the metal salt is in-situ reduced in the pores of the modified porous matrix to form one-dimensional metal nanowires; Preferably, when the metal salt in the aerogel precursor slurry B is silver nitrate, the heating reduction reaction includes a preheating stage and a heat preservation stage, the temperature of the preheating stage is 70-90 degrees, the time is 60-120 minutes, and the temperature of the heat preservation stage is 120-160 degrees, and the time is 1-8 hours.
10. A loudspeaker, characterized in that: It comprises a sound-absorbing material fixedly arranged at a preset position of the speaker, wherein the sound-absorbing material is the composite heat-conductive sound-absorbing material according to any one of claims 1 to 3 or the composite heat-conductive sound-absorbing material prepared by the preparation method according to any one of claims 4 to 9.